POLITICAL DISCUSSION THROUGH DUGDERAN CELEBRATION (CASE STUDY OF POLITICAL CULTURE IN SEMARANG CITY) - Lestari Hadiati, Tri; Harry Kistanto, Nurdien; Bahrudin, Agus (IJRDO - Journal of Social Science and Humanities Research, 2017)
Since 1970, the government of Semarang City give less attention to Dugderan Celebration. Government has little contribution in doing political discussion with people. This matter will affect the development and existence of Dugderan Celebration as local tradition and culture of Semarang area. To prevent further problem facing, interaction and synergism of the government and people, as well as devotee, supporter, and conservationists of Dugderan Celebration are needed. The stagnant development needs intensive and independent political discussion of both government and non-government agencies. This research is intended to have knowledge about political deliberation in Indonesian context, especially in Semarang City the Middle Java Province of Indonesia. The main objective of this research is to find what kinds of power sides of political deliberation. The research methods occupies mixed method, namely survey and qualitative type. Survey is conducted by asking 60 respondents throught short interviews. Obsevation and indepth interviews are then occupied to look for detailed information and context required. Research results show that the people are trying to maintain Dugderan Celebration by developing political discussion as a tradition. First, political discussion is done by holding formal public discussion with stakeholders, and second, people to people informal discussion in the village level. Besides, based on the descriptive analysis of the people perception as Semarang people of Dugderan Celebration, it could be seen that the value of the perception was 92.4%. It means that Semarang people perception of the celebration can be categorized as very good, especially in the matter of the importance of annual celebration, which is expected to happen every year, as well as Dugderan Celebration as the hallmark of Semarang City. Furthermore, based on the analysis, the positive attitude of Semarang people towards Dugderan Celebration was 78.94% which could be categorized as very good, especially in the matter of the parade and Dugderan Celebration procession. People always follow the news about the celebration from the media.